Predictors of blood pressure fall with continuous positive airway pressure (CPAP) treatment of obstructive sleep apnoea (OSA). - Robinson, G; Langford, B; Smith, D; Stradling, JR (2008)
BACKGROUND: Obstructive sleep apnoea (OSA) is associated with high cardiovascular morbidity and mortality. Randomised controlled trials have shown that, on average, treatment of OSA with continuous positive airway pressure (CPAP) reduces blood pressure (BP) by 3-5 mm Hg, although with considerable variation between individuals. No predictors of the change in BP with CPAP have been convincingly identified. This prospective study aimed to determine predictors of BP change, which might provide an insight into the aetiology of the raised BP seen in untreated OSA. METHODS: Eighty-six patients with daytime hypersomnolence warranting treatment with CPAP were recruited. 24 h mean BP (24 hMBP), subjective sleepiness, fasting venous blood samples and anthropometric measurements were assessed at baseline and after 6 months of CPAP treatment. RESULTS: The mean (SD) 24 hMBP fell at 6 months from 101.0 (10.3) mm Hg to 96.1 (9.1) mm Hg (change -4.92 mm Hg (95% CI -2.8 to -7.1)). The Epworth Sleepiness Score (ESS) fell from a median of 16 (IQR 12-18) to 4 (2-7) with a mean fall of 9.7 (95% CI 8.6 to 10.8). Several factors correlated with the fall in 24 hMBP but, after allowing for the baseline 24 hMBP, only the fall in ESS and the body mass index (BMI) remained significant independent predictors (p = 0.006 and 0.007, respectively). There was also a correlation between the fall in 24 hMBP and the fall in pulse rate (r = 0.44, p<0.001). Baseline severity of OSA, overnight hypoxia, caffeine intake or being on antihypertensive drugs were not independent predictors of a fall in 24 hMBP. CONCLUSION: Improvement in hypersomnolence and the BMI are independent correlates of the fall in 24 hMBP following CPAP therapy. Markers of initial OSA severity did not predict the fall in 24 hMBP. This suggests that sleep fragmentation and its effects may be more important than hypoxia in the pathogenesis of the hypertension associated with human sleep apnoea.